Hubungan Tingkat Kecemasan Ibu Hamil pada Masa Pandemi Covid-19 Kepatuhan Melakukan Antenatal Care di Rumah Sakit Abdul Moeloek Bandar Lampung - Ratna Dewi Puspita Sari; Sutarto Sutarto; Winda Trijayanthi Utama (Penerbit Goodwood, 2023)
Purpose: The COVID-19 pandemic has had a negative impact on physical and mental health. During this pandemic, there has been an increase in stress and anxiety in individuals who experience it. Individuals who are susceptible to stress and anxiety, one of which is pregnant women. Maternal compliance in undergoing antenatal care is one of the efforts made to determine the health of the mother and fetus during pregnancy. This pandemic is one of the reasons that make pregnant women delay starting ANC services. Based on the background of the problem, this study was conducted to find out whether there is a relationship between the level of anxiety of pregnant women during the COVID-19 pandemic with compliance with ANC at the Cipadang Village Health Center, Pesawaran Regency. Method: This study uses an observational analytic method with a cross sectional approach. Respondents were taken using total sampling technique. The data used in this study is primary data. The independent variable in this study was the level of anxiety which was assessed using the Hamilton Anxiety Rating Scale. The dependent variable of this study is the number of ANC visits obtained through the MCH book. Results: A total of 54 pregnant women with an age range of 19-42 years, a minimum score of 0 and a maximum score of 36, the number of ANC visits at least 1 time and a maximum of 16 ANC visits. The results showed that there were 6 pregnant women (11.1%) working with a junior high school education level of 22 people (40.7%). A total of 40 (74.1%) pregnant women were multigravida. The number of ANC visits was found to be the same in each group with complete and incomplete ANC visits, with an anxiety level of 36 people (66.7%). p-value is 0.013 so that there is a significant relationship between anxiety levels and ANC compliance. Limitations: The number of subjects involved in the study was still small and subjects were not involved in each trimester. Contribution: The results of this study are expected to provide information about the importance of ANC and maintain mental health for pregnant women and be input for health agencies to pay more attention to anxiety management education related to concerns of pregnant women in conducting ANC visits during the COVID-19 pandemic.